Development of articulate storyline-based interactive learning media on arithmetic sequences and series - Ayustika Raudatul Jannah; Susi Setiawani; Rafiantika Megahnia Prihandini (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2023)
Research in learning media development is driven by the common problem of student disengagement, which hinders their understanding of the material. The specific problem addressed in this research is students' lack of attention and comprehension while studying arithmetic sequences and series. The purpose of this study is to document the process and outcomes of developing interactive learning media using Articulate Storyline specifically for the material on sequences and arithmetic series. The research follows the Research and Development (R&D) approach, employing the Thiagarajan model (Model 4-D) consisting of four stages: 1) the definition stage (define), 2) the design stage (design), 3) the development stage (development), and 4) the dissemination stage (disseminate). The research was conducted with a sample of 31 students from class X B at SMA Tunas Luhur. The results of the media validity test showed a score of 4.82, indicating high validity. Furthermore, the practicality and effectiveness tests conducted with both small and large groups achieved a perfect score of 100% in all aspects. This research indicates that the interactive learning media for arithmetic sequences and series based on Articulate Storyline meet the criteria of validity, practicality, and effectiveness.